Prospective study of vaginal dilator use adherence and efficacy following radiotherapy. Issue 1 (July 2015) - Law, Ethel; Kelvin, Joanne F.; Thom, Bridgette; Riedel, Elyn; Tom, Ashlyn; Carter, Jeanne; Alektiar, Kaled M.; Goodman, Karyn A.
Abstract Background and purpose Vaginal stenosis (VS) after pelvic radiotherapy (RT) can impair long-term quality of life. We prospectively assessed adherence and efficacy of vaginal dilator (VD) use in women after pelvic RT. Material and methods Women with gastrointestinal (n = 63) and gynecologic (n = 46) cancers self-reported use and VD size in monthly diaries for 12 months after radiotherapy. Adherence was measured as actual VD use out of recommended times over 12 months (3×/week × 52 weeks = 156). Results Among 109 participants, aged 28–81 years (median, 58 years), mean percent adherence over 12 months was 42% (95% confidence interval [CI], 36–48%). Adherence was highest in the first quarter (56%), but fell to 25% by the fourth. Disease type, treatment sequence, and chemotherapy were predictors of adherence (all P < .05). Eighty-two percent maintained pre-RT VD size at 12 months; of 49% with a decrease in VD size at 1 month post-RT, 71% returned to pre-RT VD size at 12 months. Disease type, younger age, and increased adherence at 6 months were associated with maintaining or returning to pre-RT size at 12 months (all P ⩽ .05). Conclusion VD use is effective in minimizing VS, but adherence at 12 months was poor. Studies evaluating methods of improving adherence and determining the optimal frequency and duration of use are needed.